Middleware for next generation urban traffic control. - CAHILL, VINNY; HARRINGTON, ANTHONY CHRISTOPHER (ETC, 2004)
Next generation Urban Traffic Control (UTC) systems should be flexible in their ability to handle new and improved sensor information that is beginning to become available from cameras, GPS devices, and other sources. They should equally be open to supporting a variety of different traffic management policies, informed by this increasingly availabile sensor data, to optimise the flow of traffic in an urban environment. The focus of the UTC-NG project in Trinity College Dublin is on exploring the design of next- generation UTC systems. With the expected increase in the deployment of a variety of different sensor technologies, key to such a design is that it should address this diversity. A consequence of supporting a variety of sensor types, is that the design also needs to accommodate a variety of ways of processing the information provided by these sensors to form an accurate view of the current state of the UTC system and ultimately to implement different traffic control policies. Moreover, as the variety and accuracy of sensor data improves and new sensor fusion techniques are developed, it should be possible to easily exploit this new information. In a similar way, different policies to optimise the movement of traffic through the system may need to be incorporated over time. This paper describes how the UTC-NG project is addressing these problems through the use of middleware. Middleware is a collection of services that can be used by application developers (in this case the developers of specific UTC systems) to build a particular UTC application. In the case of middleware for next-generation UTC, the middleware will provide services for sensor fusion, reasoning about the system state, and communication embodied in an appropriate programming model and should support a plug and play' approach to choosing the right services for different systems. A stigmergic model is being used to address the complex interaction between collections of junctions and consequently to allow optimisation of the overall traffic flow in a UTC system. In such a stigmergic model, a junction will follow simple rules, taking in appropriate information from fixed and mobile sensors as well as from neighbouring junctions and in turn informing neighbouring junctions of changes it is making to traffic light phases under its control. Currently, a prototype implementation of a simulator for the UTC-NG project is being undertaken. The goal of this simulator is to exercise the middleware platform and provide valueable insight into how a number of sensors and sensor fusion techniques can be supported and also aid in the adaptation of the set of simple rules, which enables optimisation of traffic flow, to a particular traffic management policy.
Proceedings of the European Transport Conference (ETC),
European Transport Conference (ETC),
PUBLISHED
Strasbourg, France
Keywords: Computer Science